AVRUPA BİRLİĞİ TEMEL HAKLAR ŞARTI - Hakan Taşdemir (Ankara Avrupa Çalışmaları Dergisi)
ABSTRACTThe article studies the Charter of the Fundamental Rights of the European Union (EU). In this framework, first o f ali, the policies and attitudes o f the EU towards fundamental rights are studied. In this way, the historical development of fundamental rights/human rights in the EU are showed. Then, the article focuses on the process of preparation of the Charter. After that, the article gives attention to the Charter, its content and improvements which occure with the Charter. Later, the article examines the effects of the Charter on Turkey. Because o f being a candidate State to the EU, the Charter is important for Turkey, too. At the end, a general evaluation is made about the Charter and its importance.GİRİŞİnsan hakları, kişinin salt insan olması açısından taşıdığı değerin vurgulanmasıdır. Sahip olunan bu özgürlük değerlerinin başkalarınca tanınması ve etkilere karşı korunması da insan haklarıdır.